DEMOGRAPHIC AND PATHOLOGICAL CHARACTERISTICS OF GASTRIC CARCINOMAS – A Three-Year Single Center Experience - Ognjenovic, Ljubomir; Sumkovski, Aleksandar; Trajkovski, Gjorgi; Bushinovska, Jasna; Nikolova, Dafina; Hadzi-Manchev, Dragan; Dzambaz, Darko (Journal of Morphological Sciences; Vol 3 No 2 (2020): JMS, 2020)
Introduction:Despite the decline in incidence and mortality rate in recent years, gastric carcinoma (GC) remains one of the leading causes of cancer-related deaths worldwide, especially in developing countries. The aim of this study was to present the clinic-pathological characteristics of gastric carcinomas in Patients in R. of North Macedonia. Material and methods :  One hundred and forty-nine patients with gastric carcinoma were included in the study. Sixty-one patients underwent subtotal gastric resection with lymphadenectomy, and 88 patients underwent total gastrectomy with lymphadenectomy. For every patient tumor localization, TNM classification, grade and stage were determined. The parameters of the TNM classification (AJCC Cancer Staging 2017) were obtained from the archive histopathological reports of the Institute of Pathology in Skopje, and for the clinical stage, we used patientâ€™s files from the University Clinic for Abdominal Surgery in Skopje. Results:The most common intragastric location of gastric carcinomas was cardia in 61 (40.94%) patients, followed by antral/pyloric carcinoma location in 51 (34.23%) patients and corpus location in 37 (24.83%) patients. According to the T state (local tumor growth), more than half of the examined patients 84 (56.38%) were in T4 state of the disease. Presence of positive regional lymph nodes was detected in 113 (75.84) patients, and negative in 36 (24.16%) patients. The majority of the patients that comprised the analyzed group had poor differentiated gastric carcinoma 81 (54.36%), and 88 (59.06%) were in Stage III of the disease. Key words: gastric carinoma, TNM, grade, stage